Pengaruh Event Marketing, Brand Image, dan Perilaku Konsumtif terhadap Keputusan Pembelian Photocard pada Reseller Chaehzelnut Serta Dampaknya terhadap Kepuasan Pelanggan - Andini Eka Saputri; Wahid Akbar Basudani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze in depth the influence of event marketing, brand image, and consumer behavior on consumer purchasing decisions, as well as to explore the indirect influence of these three variables on customer satisfaction through purchasing decisions on Chaehzelnut reseller consumers. The research approach used is quantitative, with data collection through questionnaires distributed to 109 respondents selected using the Simple Random Sampling technique so that each member of the population has an equal opportunity to be sampled. The collected data were then analyzed using the SmartPLS application version 4.1.1.8 to test the relationship between variables through the Partial Least Squares (PLS) model. The results of the analysis show that event marketing has a negative and significant influence on purchasing decisions, which indicates that promotional activities through events do not always increase consumer purchasing interest. In addition, event marketing also does not have a significant effect on customer satisfaction through purchasing decisions. Conversely, brand image and consumer behavior are proven to have a positive and significant influence on purchasing decisions, which means that the stronger the brand image and the higher the level of consumer consumer behavior, the higher their tendency to buy the product. These two variables also have a positive indirect influence on customer satisfaction through purchasing decisions, indicating that purchasing decisions act as a mediating variable in the relationship.